Efeito da redução de comportamento sedentário associado ao treinamento multicomponente na composição corporal de idosos: ensaio clínico randomizado controlado - Lee, Stefany (2023)
Introduction: Body composition changes occur in the aging process leading to an increase in fat mass and a decline in lean mass. Physical exercise can cause changes in body composition, but it is unclear whether reducing sedentary behavior (SB) also produces positive effects. Objective: To assess whether adopting self-management strategies (SMS) associated with a multicomponent training compared to a multicomponent training alone can improve the body composition of older adults who were physically active before the pandemic. Methods: A single-blind, randomized, controlled clinical trial was performed. Forty-five older adults were divided into two groups: Multi and Multi+SMS. The Multi (aerobic, muscular resistance, balance and flexibility) lasted 16 weeks (3x week, 50 minutes/session). The SMS consisted of goals and weekly telephone follow-up calls. Body composition was assessed by dual-energy X-ray absorptiometry (DXA) and the time spent in SB using the ActivPAL3™ accelerometer. A generalized mixed linear model was performed (fixed factors: time, group and interaction and random factor: subjects). Results: Both groups reduced time in SB, increased lean mass index, reduced the fat mass index and fat mass percentage. There was no change in the appendicular lean mass index. Conclusion: SMS to reduce SB did not potentiate the effects of Multi on the body composition of older adults. Offering physical exercise programs to older adults who have similar characteristics to those in our study may be enough to reduce SB and improve their body composition.